Establishment and large-scale validation of a three-dimensional tumor model on an array chip for anticancer drug evaluation - Xiao, Rong-Rong; Jin, Lei; Xie, Nan; Luo, Piaopiao; Gao, Wenjie; Tu, Pengfei; Ai, Xiaoni (Frontiers in Pharmacology, 2022)
Two-dimensional (2D) tumor model has always poor predicted drug response of animal model due to the lack of recapitulation of tumor microenvironment. Establishing a biomimetic, controllable, and cost-effective three-dimensional (3D) model and large-scale validation of its in vivo predictivity has shown promises in bridging gap between the 2D model and animal model. Here, we established a matrigel-based 3D micro-tumor model on an array chip for large-scale anticancer drug evaluation. Compared with the 2D tumor model, the 3D tumor model on the chip showed more biomimetic cell morphology, slower proliferation kinetics, and comparable reproducibility. Next, the results of the chemotherapeutic evaluation of 18 drugs against 27 cancer cell lines showed 17.6% of drug resistance on the 3D tumor model. Moreover, the evaluation results of targeted drugs showed expected sensitivity and higher specificity on the 3D tumor model compared with the 2D model. Finally, the evaluation results on the 3D tumor model were more consistent with the in vivo cell-derived xenograft model and excluded the 95% false-positive results from the 2D model. Overall, the matrigel-based 3D micro-tumor model on the array chip provides a promising tool to accelerate anticancer drug discovery.